Trends in caries and associated variables among young Israeli adults over 5 decades - Sgan-Cohen HD, Katz J, Horev T, Dinte A, Eldad A (Blackwell Synergy, 2000)
This study was conducted among a representative sample of 7139 21- year-old Israeli adults, upon release from compulsory military service. Data were collected between 1994 and 1997. The average DMFT level found was 8.49º4.95. Untreated caries (according to the D component of DMFT) was 2.25º2.90 and significantly higher among males. Untreated caries was also significantly associated with geographic origin: higher among subjects of African or former USSR descent; and with family size: higher among subjects with four or more siblings; with education: caries was higher among subjects with less than 12 years of schooling; and with smoking: caries was more extensive among those who smoked (P,0.0001 for all the associations). Caries severity (DMFT) was found to be significantly associated with father’s country of origin and number of siblings (highest among subjects of Asian and African descent and those who had four or more Key words: dental caries; dental siblings).